Evaluasi kebijakan pembiayaan ultra mikro dalam perspektif hukum ekonomi syariah: isu, tantangan, dan solusi - Maulidina, Marissa Alifta; Farroh, Akhmad Hasan (Maliki Interdisciplinary Journal, 2025)
The Ultra Micro Financing Program (UMi) is a government initiative that aims to reach micro-entrepreneurs who have not been touched by banking services. However, the implementation of this policy faces a number of obstacles, especially related to the application of Islamic economic law principles, such as the use of contracts that are less in accordance with sharia and the limited understanding of recipients of the concept of sharia finance. This study aims to examine the effectiveness of the implementation of the UMi program based on the perspective of Islamic economic law, identify various problems and obstacles, and offer solutions that are in accordance with sharia principles. The method used is qualitative with a literature study approach. The results of the study indicate violations in the implementation of contracts and a weak understanding of sharia principles among business actors. Therefore, it is recommended to strengthen regulations, increase sharia education, and active collaboration between sharia financial institutions, the government, and academics